A retrospective study on equine cases referred to University Veterinary Hospital, UPM from 2005-2009 - Mohd Said, Fauziah; Mohd Adzahan, Noraniza (2010)
A retrospective study was carried out to determine the prevalence and total number of equine cases reported to University Veterinary Hospital (UVH), UPM from year 2005 to 2009 and to determine the relationship between case occurrence and type of purpose of horses. Data were gathered from UVH records. A total of 1,521 equine cases were recorded from 22 horse establishments, involving eight different purposes of horses with eight and 30 categories of general and specific clinical problems, respectively. The occurrence of equine cases in year 2005 was 228 (15.0%), 2006 was 216 (14.2%), 2007 was 372 (24.5%), 2008 was 340 (22.4%) and 2009 was 365 (24.0%). The most common general clinical problems were musculoskeletal problems, traumatic injuries and gastrointestinal problems. However, based on specific conditions, traumatic injuries showed the highest percentage of occurrence within the 5 years.